Research on Correcting Eccentric Load of the Internal Gear Tooth Surface by Orthogonal Tests Based on Neural Network Optimization - Wang Zhenbo; Zheng Peng; Liu Yifei (Jixie chuandong)
In order to solve the problem of tooth surface eccentric load caused by shaft deflection angle of large internal meshing gears of the shield machine, the tooth surface equation of comprehensively modified tooth surface is given, and the method of neural network combined with orthogonal test is proposed to screen and predict the tooth surface modification parameters. In this method, the tooth profile modification and tooth direction modification are no longer regarded as independent variables, and the eccentric load on the tooth surface can be transformed into the load evenly distributed on the tooth surface. Through the contact analysis of the modified gear by the finite element method, it is found that this method can effectively reduce the excessive local stress on the tooth surface caused by the shaft deflection angle and reduce the transmission error. The optimal tooth surface modification parameter value can be found at one time, which avoids the high cost of meshing experiment for the internal meshing gear of large shield machines.